2010
DOI: 10.1080/00087114.2010.10589739
|View full text |Cite
|
Sign up to set email alerts
|

Production of colchicine induced tetraploids inVicia villosaroth

Abstract: Seeds V. villosa (hairy vetch) were treated with 0.005% colchicine and 12% tetraploid plants (2n=4x=28) were obtained. Besides two chimeric plants, one of them consisted of diploid, triploid, tetraploid, hexaploid, heptaploid, octoploid roots and the other diploid and triploid roots were also obtained in hairy vetch. Tetraploid plants were determined by the chromosome numbers in the root tips which were confi rmed by studies conducted in the pollen mother cells (PMCs). Chromosome irregularities in the PMCs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 27 publications
4
14
0
1
Order By: Relevance
“…Indeed, we did find that neopolyploidy significantly delayed the time to first flower. This result is similar to the findings of some studies that have recorded flowering times of neopolyploids, for example in Vicia villosa (Fabaceae; Tulay and Unal, ), Heuchera grossulariifolia (Saxifragaceae; Oswald and Nuismer, ), Achillea borealis (Asteraceae; Ramsey, ), Chamerion angustifolium (Martin and Husband, ), and multiple species in the genus Miscanthus (Poaceae; Chae et al., ). However, other studies have found either that genome duplication does not alter flowering timing, as in Acacia mangium (Nghiem et al., ) and Chamerion angustifolium (Husband et al., ), or that there are mixed results when neopolyploids are derived via hybridization, as in Brassica napus (Brassicaceae; Hansen and Earle, ) and Cucumis hybrid (Cucurbitaceae; Chen et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, we did find that neopolyploidy significantly delayed the time to first flower. This result is similar to the findings of some studies that have recorded flowering times of neopolyploids, for example in Vicia villosa (Fabaceae; Tulay and Unal, ), Heuchera grossulariifolia (Saxifragaceae; Oswald and Nuismer, ), Achillea borealis (Asteraceae; Ramsey, ), Chamerion angustifolium (Martin and Husband, ), and multiple species in the genus Miscanthus (Poaceae; Chae et al., ). However, other studies have found either that genome duplication does not alter flowering timing, as in Acacia mangium (Nghiem et al., ) and Chamerion angustifolium (Husband et al., ), or that there are mixed results when neopolyploids are derived via hybridization, as in Brassica napus (Brassicaceae; Hansen and Earle, ) and Cucumis hybrid (Cucurbitaceae; Chen et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…If diploid plants were pollinated with pollens of tetraploid plants, the fruit set rate, seed count and germination ability remarkably decreased compared to reciprocal crosses and crosses between controls (Table 3). Similar results were already reported in other tetraploid plants, such as Citrullus lanatus (Jaskani et al 2005) and Vicia villosa (Tulay & Unal 2010). Our findings are most likely connected with the ploidy status of regenerated plants.…”
supporting
confidence: 79%
“…Colchicine treated plants of alocasia (Alocasia macrorrhizos) showed slow growth and smaller size plants than control because of disturbance of normal cell division by the penetration of colchicine into the apical meristems cells (Thao et al, 2003). Previous findings reported reduced plant height in cotton (Gossypium arboreum) and hairy vetch (Vicia villosa) probably resulting from reduced respiratory ratio, metabolic enzyme's activity and restriction in auxin supply to cell under different colchicine treatment (Rauf et al, 2006;Tulay and Unal, 2010). Colchicine significantly decreases the number of leaves per plant, leaf area, length and width but it increases leaf thickness in 0.3% concentrations.…”
Section: Discussionmentioning
confidence: 97%